Effects of environmental factors on the toxicity of pesticides to zebrafish embryos - Andrade, Thayres de Sousa (2015)
During the last century mean global temperatures have been increasing. According to the predictions, the temperature change is expected to exceed 1.5ºC in this century and the warming is likely to continue. Freshwater ecosystems are among the most sensitive mainly due to changes in the hydrologic cycle and consequently changes in several physico-chemical parameters (e.g. pH, dissolved oxygen). Alterations in environmental parameters of freshwater systems are likely to affect distribution, morphology, physiology and richness of a wide range of species leading to important changes in ecosystem biodiversity and function. Moreover, they can also work as co-stressors in environments where organisms have already to cope with chemical contamination (such as pesticides), increasing the environmental risk due to potential interactions. Therefore, the objective of this work was to evaluate the effects of climate change related environmental parameters on the toxicity of pesticides to zebrafish embryos. The following environmental factors were studied: pH (3.0-12.0), dissolved oxygen level (0-8 mg/L) and UV radiation (0-500 mW/m2). The pesticides studied were the carbamate insecticide carbaryl and the benzimidazole fungicide carbendazim. Stressors were firstly tested separately in order to derive concentration- or intensity-response curves to further study the effects of binary combinations (environmental factors x pesticides) by applying mixture models. Characterization of zebrafish embryos response to environmental stress revealed that pH effects were fully established after 24 h of exposure and survival was only affected at pH values below 5 and above 10. Low oxygen levels also affected embryos development at concentrations below 4 mg/L (delay, heart rate decrease and edema), and at concentrations below 0.5 mg/L the survival was drastically reduced. Continuous exposure to UV radiation showed a strong time-dependent impact on embryos survival leading to 100% of mortality after 72 hours of exposure. The toxicity of pesticides carbaryl and carbendazim was characterized at several levels of biological organization including developmental, biochemical and behavioural allowing a mechanistic understanding of the effects and highlighting the usefulness of behavioural responses (locomotion) as a sensitive endpoint in ecotoxicology. Once the individual concentration response relationship of each stressor was established, a combined toxicity study was conducted to evaluate the effects of pH on the toxicity of carbaryl. We have shown that pH can modify the toxicity of the pesticide carbaryl. The conceptual model concentration addition allowed a precise prediction of the toxicity of the jointeffects of acid pH and carbaryl. Nevertheless, for alkaline condition both concepts failed in predicting the effects. Deviations to the model were however easy to explain as high pH values favour the hydrolysis of carbaryl with the consequent formation of the more toxic degradation product 1- naphtol. Although in the present study such explanatory process was easy to establish, for many other combinations the “interactive” nature is not so evident. In the context of the climate change few scenarios predict such increase in the pH of aquatic systems, however this was a first approach focused in the lethal effects only. In a second tier assessment effects at sublethal level would be sought and it is expectable that more subtle pH changes (more realistic in terms of climate changes scenarios) may have an effect at physiological and biochemical levels with possible long term consequences for the population fitness.